Bài làm:
Ta có: \(\left(\frac{1}{2}x+\frac{3}{4}\right)^2\div\left(-\frac{3}{14}\right)=-\frac{7}{24}\)
\(\Leftrightarrow\left(\frac{1}{2}x+\frac{3}{4}\right)^2=\frac{1}{16}=\left(\frac{1}{4}\right)^2\)
\(\Leftrightarrow\orbr{\begin{cases}\frac{1}{2}x+\frac{3}{4}=\frac{1}{4}\\\frac{1}{2}x+\frac{3}{4}=-\frac{1}{4}\end{cases}}\Leftrightarrow\orbr{\begin{cases}\frac{1}{2}x=-\frac{1}{2}\\\frac{1}{2}x=-1\end{cases}}\Rightarrow\orbr{\begin{cases}x=-1\\x=-2\end{cases}}\)
(\(\frac{1}{2}\).x+\(\frac{3}{4}\))2: \(\frac{-3}{14}\)=\(\frac{-7}{24}\)
(\(\frac{1}{2}\).x+\(\frac{3}{4}\))2 =\(\frac{1}{16}\)
(\(\frac{1}{2}\).x+\(\frac{3}{4}\))2=(\(\frac{1}{4}\))2
\(\hept{\begin{cases}\frac{1}{2}.x+\frac{3}{4}=\frac{1}{4}\\\frac{1}{2}.x+\frac{3}{4}=\frac{-1}{4}\end{cases}}\)<=>\(\hept{\begin{cases}\frac{1}{2}.x=\frac{1}{4}-\frac{3}{4}\\\frac{1}{2}.x=\frac{-1}{4}-\frac{3}{4}\end{cases}}\)<=>\(\hept{\begin{cases}\frac{1}{2}.x=-\frac{1}{2}\\\frac{1}{2}.x=-1\end{cases}}\)
<=>\(\hept{\begin{cases}x=\frac{-1}{2}:\frac{1}{2}=-1\\x=-1:\frac{1}{2}=-2\end{cases}}\)